Enhanced anti-inflammatory activity of chlorogenic acid via folic acid-TPGS-modified liposomes encapsulation: characterization and In vivo evaluation on colitis mice - Li, Qing-qing; Yan, Jia-hui; Zhou, Zhi-e; Geng, Xiang; Xiong, Jian-hua (Frontiers in Pharmacology, 2024)
Chlorogenic acid (CGA) has been identified to possess salient anti-inflammatory, antioxidant, and anticancer attributes. However, its application is limited by its instability and low bioavailability. Liposomes have been considered effective pharmaceutical delivery vehicles due to their ability to continuously release loaded drugs, improve drug stability, and display good biocompatibility. They can be easily modified by other small molecules to acquire additional biological functions. In this study, we developed and characterized folic acid-TPGS-modified chlorogenic acid liposome (FTCLP) and evaluated its anti-inflammatory activity. The successful encapsulation of CGA within FTCLP was confirmed through examination using electron microscopy, fourier-transform infrared spectroscopy (FTIR), and differential scanning calorimetry (DSC). The FTCLP exhibited an encapsulation efficiency (EE) of 84.85 ± 1.20% and a drug loading (DL) of 11.67 ± 0.04%. The particle size of FTCLP was determined to be 150.63 ± 0.71 nm, with a polydispersity index (PDI) of 0.198 ± 0.02 and a zeta potential of 2.61 ± 0.38 mV. The in vitro release profile followed the Higuchi model, indicating sustained-release characteristics. The in vivo study demonstrated that FTCLP treatment was effective in improving the symptoms of dextran sulphate sodium (DSS)-induced inflammatory response, as evidenced by mitigation of weight loss, reduction in the disease activity index (DAI) score, restoration of colon length, and attenuation of colon tissue damage. Furthermore, the levels of pro-inflammatory cytokines, including interferon-gamma (INF-γ), interleukin-1 beta (IL-1β), and interleukin-6 (IL-6), were markedly diminished in both the serum and colon tissue. FTCLP was also observed to suppress the expression of INF-γ, IL-1β, IL-6, tumor necrosis factor-alpha (TNF-α), and nuclear factor kappa B (NF-κB) p65, while concomitantly upregulating the expression of Janus kinase (JAK) and signal transducer and activator of transcription 3 (STAT3). Besides, the administration of FTCLP was found to result in an increase in the abundance of 2 Lactobacillaceae and Peptostreptococcaceae, while decreasing the abundance of Bacteroidaceae, Rikenellaceae, and Helicobacteraceae. Overall, following encapsulation of CGA within liposomes, FTCLP revealed favorable stability and sustained release properties, and enhanced the anti-inflammatory effects by modulating multiple inflammation-related biomarkers. FTCLP has the potential to be a safe and effective drug for targeted therapy of colitis.